2021
DOI: 10.1186/s12915-021-01160-8
|View full text |Cite
|
Sign up to set email alerts
|

Short single-stranded DNAs with putative non-canonical structures comprise a new class of plasma cell-free DNA

Abstract: Background Cell-free DNA (cfDNA), which is extracellular DNA present in the circulating plasma and other body fluids, is currently investigated as a minimally invasive, highly informative biomarker. While nucleosome-sized cfDNA fragments have been investigated intensively, shorter DNA fragments in the plasma have not been studied due to several technical limitations. Results We aimed to investigate the existence of shorter cfDNA fragments in the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 68 publications
4
43
2
Order By: Relevance
“…Using MB-ssDNA, we observed an average 35-fold higher recovery of US fragments compared to the other methods (86-, 13-, and fivefold higher as compared to SC-dsDNA, MB-dsDNA, SC-ssDNA, respectively). A report released during the revision of this manuscript using alternative chemistry for DNA extraction also suggested a better recovery of US fragments (Hisano et al 2021). The US fragments observed in our study were relatively enriched in plasma from healthy individuals as compared to cancer patients (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Using MB-ssDNA, we observed an average 35-fold higher recovery of US fragments compared to the other methods (86-, 13-, and fivefold higher as compared to SC-dsDNA, MB-dsDNA, SC-ssDNA, respectively). A report released during the revision of this manuscript using alternative chemistry for DNA extraction also suggested a better recovery of US fragments (Hisano et al 2021). The US fragments observed in our study were relatively enriched in plasma from healthy individuals as compared to cancer patients (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…However, sequences shorter than 50bp may have greater intergenic proportion which would result in the dilution of sequences in coding regions for SPRI extracted samples ( Figure 4 C). During our manuscript revisions we discovered that three other research groups (one unpublished) also isolated ultrashort single-strand fragments in plasma using distinctly different methods ( Cheng et al., 2021 ; Hisano et al., 2021 ; Hudecova et al., 2021 ). There would be interest to cross-compare these methods in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly clear during the last years that another cfDNA population exists in plasma that might exhibit diagnostic potential: ultrashort single-stranded cfDNA fragments up to 100 bp [ 20 , 167 , 168 , 169 , 170 ]. These fragments are often omitted by conventional library preparation due to the adapter ligation process that needs double strands and/or applied size selection procedures.…”
Section: Epigenetic-based Biomarkers In Liquid Biopsymentioning
confidence: 99%
“…An early study employing single-stranded library preparation and subsequent sequencing demonstrated that short cfDNA molecules directly footprint TFBS occupancy [ 20 ]. Recent efforts optimizing different DNA extraction and library preparation procedures independently demonstrated the presence of this novel population of cfDNA molecules that might inform on gene regulatory regions and DNA secondary structures [ 168 , 169 , 170 ].…”
Section: Epigenetic-based Biomarkers In Liquid Biopsymentioning
confidence: 99%